Acute wiiitis representing as thrombosis of the inferior vena cava and left pelvic veins. (August 2015) - Brodmann, M; Gary, T; Hafner, F; Eller, P; Deutschmann, H; Pilger, E; Seinost, G
Deep venous thrombosis as a result of venous wall injury provoked by trauma is a common finding. It often occurs in patients with sportive overstraining, caused by over fatigue of the body structures. In 2007, the entity of "acute wiiitis" was first described in a letter to the New England Journal of Medicine . Acute wiiitis sums up all affections, mainly skeletal and muscle affections, provoked by playing Nintendo Wii, a very common and loved video-game system. Deep venous thrombosis as a consequence of Nintendo Wii has not been described so far. We present a patient with a massive free floating thrombus of the left pelvic veins originating from the gluteal veins and reaching into the inferior vena cava after playing Nintendo Wii.